Generalized hybrid Mehler-Fock-type integral transformation of the first kind and its applications - Konet, I. M.; Конет, І. М. (Institute of Mathematics, NAS of Ukraine, 2007)
We introduce a generalized hybrid integral transformation of the Mehler-Fock type on a segment [0; R] with n conjugate points. We consider examples of application of this transformation to the solution of typical singular boundary-value problems for linear partial differential equations of the second order in piecewise-homogeneous media.